Optimization of FSP parameters to fabricate AA7075-based surface composites using Taguchi technique and TOPSIS approach. Issue 5 (4th March 2023) - Suganeswaran, K.; Muthukumar, P.; Parameshwaran, R.; Nithyavathy, N.; Mohanraj, T.; Deepandurai, K.
Abstract: Aluminum alloy-based surface composites processed by friction stir processing with enhanced hardness and impact energy is potentially suitable for aircraft and automotive applications. This behavior is improved by applying design of experiments (DOEs) in finding the suitable combination of process parameters. The influence of tool rotational speed, transverse speed, tilt angle, plunging depth and number of passes on hardness and impact energy are determined via Taguchi. It is identified that No. of pass plays a major contribution based on ANOVA. Single optimal parameter obtained through TOPSIS is employed to fabricate the composites with different volume ratios of WO3 and SiC particulates. Microstructural characterization of all the defect free surface composites depicts wide and homogenous dispersion of reinforcement particulates. Surface hybrid composite specimen comprising both WO3 and SiC particles significantly raises the microhardness to 214VHN attributed to the homogenous dispersion strengthening and grain boundary pinning mechanism. The specimen tends to show enhanced impact energy (12.3 J) due to extensive load bearing capacity of the reinforcements.